Fractography of glasses and ceramics VI : proceedings of the sixth Conference on the Fractography of Glasses and Ceramics, June 5-8, 2011, Jacksonville, Florida - Conference on the Fractography of Glasses and Ceramics 2011 : Jacksonville, Fla.); Varner, James R.; Wightman, Marlene; Wiley eBooks (Hoboken, N.J. : Wiley, 2012)
Provides an excellent one-stop resource for understanding the most important current issues in the research and applications of fractography of glasses and ceramics.
Triple Blind Fractography Study of Yttria-Stabilized Zirconia Thin-Film-Modified PorcelainResidual Failure Due to Incomplete Sintering of Vitreous China Plumbing Fixtures; Laminate Design Effects on the Fracture Patterns of Impact Resistance Glass Panels; Application of Fractography in Pharmaceutical Industry; Using Replicas in Fractography of Glasses and Ceramics-Advantages and Pitfalls; Author Index.
Includes bibliographical references and author index.
John Wiley and Sons
Keywords: Glass -- Fracture -- Congresses; Ceramic materials -- Fracture -- Congresses; Fractography -- Congresses; Ceramic materials -- Fracture -- Congresses; Fractography -- Congresses; Glass -- Fracture -- Congresses; Engineering; Civil engineering; TECHNOLOGY & ENGINEERING -- Material Science; Ceramic materials -- Fracture; Fractography; Glass -- Fracture; Electronic books